1997
DOI: 10.1590/s1516-31801997000600006
|View full text |Cite
|
Sign up to set email alerts
|

CEA as a prognostic index in colorectal cancer

Abstract: Although the tumor stage is today the most valuable prognostic variable in colorectal cancer, the preoperative CEA value can provide some additional information in the prognosis of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 11 publications
(2 reference statements)
3
34
0
2
Order By: Relevance
“…Despite the controversy concerning the validity of measuring the pre-operative levels of CEA, our studies emphasize their value and demonstrate an association between higher levels of CEA and poorer prognosis (12,42) . Some research contradicts these findings and show that 14% to 56% of CRC cases can present with normal blood levels of CEA (44,47) .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Despite the controversy concerning the validity of measuring the pre-operative levels of CEA, our studies emphasize their value and demonstrate an association between higher levels of CEA and poorer prognosis (12,42) . Some research contradicts these findings and show that 14% to 56% of CRC cases can present with normal blood levels of CEA (44,47) .…”
Section: Discussionmentioning
confidence: 57%
“…The results obtained in the present study support a correlation between the Dukes (9) , TNM (18) and morphofunctional classifications and increased CEA levels in advanced stages of neoplasia. These results demonstrate a rise in CEA levels in the blood, which is associated with disease progression, although, current studies relating CEA and prognostic classification are controversial (5,12,44) . An increase in CEA levels after complete resection can suggest cancer recurrence (8) , but there is a subset of CRC tumors that produce a small quantity of CEA and blood levels remain normal.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Forones et al 14 retrospectively studied peripheral CEA levels in 83 patients with regard to prognoses for colorectal cancer and correlated these with the Dukes staging. They found that CEA had a capacity to differentiate stage A from stage C and C from B, but not A from B.…”
Section: Discussionmentioning
confidence: 99%
“…24,27 Contradizem estes achados pesquisas mostrando que 14% a 56% dos casos de CCR podem cursar com nível sérico de CEA normal. 23,44 A correlação dos níveis séricos do CEA pré-operatórios com o está-dio do carcinoma colorretal permanece polêmica.…”
Section: Estadiamentounclassified